Vitamina B3 e bioinsumo de microalgas na produção de mudas de manjericão - FERREIRA, Elen Saturnino; BINOTTI, Flávio Ferreira da Silva; SALLES, Jussara Souza; BINOTTI, Eliana Duarte Cardoso; COSTA, Edilson; VENDRUSCOLO, Eduardo Pradi (ANAIS DO ENIC, 2024)
-